2022
DOI: 10.1039/d2sc05031e
|View full text |Cite
|
Sign up to set email alerts
|

Capture of activated dioxygen intermediates at the copper-active site of a lytic polysaccharide monooxygenase

Abstract: Superoxo and hydroperoxo intermediates were cryotrapped at the copper active site of lytic polysaccharide monooxygenase using neutron protein crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 110 publications
(195 reference statements)
1
22
0
Order By: Relevance
“…6b). This confirms that in this conformation His147 remains neutral at low pH (Schro ¨der et al, 2022), as also shown by analysis of high-resolution X-ray structures (Banerjee et al, 2022).…”
Section: Residues Near the Active Site: Tyr164 And His147supporting
confidence: 86%
See 1 more Smart Citation
“…6b). This confirms that in this conformation His147 remains neutral at low pH (Schro ¨der et al, 2022), as also shown by analysis of high-resolution X-ray structures (Banerjee et al, 2022).…”
Section: Residues Near the Active Site: Tyr164 And His147supporting
confidence: 86%
“…Neutron protein crystallography is a powerful tool for investigating protein chemistry because it directly locates H-atom positions in a protein structure (Schro ¨der et al, 2018). Early X-ray and neutron crystallographic studies of LPMOs from the AA9 family have focused on understanding the activation of O 2 by Neurospora crassa LPMO 9D (NcAA9_D) in the absence of substrate (Bodenheimer et al, 2017;O'Dell, Swartz et al, 2017;O'Dell, Agarwal et al, 2017;Schro ¨der et al, , 2022. In addition to the direct determination of protonation states, these structures have revealed the geometry and the chemical nature of the initial Cu-O 2 À and Cu-O 2 H intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 O 2 molecule was placed such as to interact with His155 and Gln/Glu164 based on the results of previous computational studies. ,,, These previous studies have shown that LPMO reactivity is associated with an intricate fluctuating H-bonding network, which in the current model depends on the protonation state of His155 (HID or HIE tautomeric forms or HIP) and Glu164 (for the mutant). Recent neutron diffraction and high-resolution X-ray diffraction studies on other AA9s have shown His155 likely does not occur in the double protonated form, not even at acidic pH. , The initial reactivity calculations along the HO–OH bond cleavage pathway featured His155 with the proton at the N ε position (HIE). The choice of HIE155 is supported by neutron diffraction studies , of other AA9s from Neurospora crassa and the higher stability of HIE compared to HID in QM/MM calculations .…”
Section: Resultsmentioning
confidence: 99%
“…Recent neutron diffraction and high-resolution X-ray diffraction studies on other AA9s have shown His155 likely does not occur in the double protonated form, not even at acidic pH. , The initial reactivity calculations along the HO–OH bond cleavage pathway featured His155 with the proton at the N ε position (HIE). The choice of HIE155 is supported by neutron diffraction studies , of other AA9s from Neurospora crassa and the higher stability of HIE compared to HID in QM/MM calculations . The lack of similar data on the Q164E mutant motivated us to explore both protonation states of Glu164.…”
Section: Resultsmentioning
confidence: 99%
“…This alleviates the sample volume requirement by as much as a factor of ten. A few neutron crystal structures of LPMOs have already been determined; however, none of them is perdeuterated, enabling mapping of only select hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%